Immunobiology and Application of Aloe vera-Based Scaffolds in Tissue Engineering - Darzi, Saeedeh (Int J Mol Sci, 2021)
Aloe vera (AV), a succulent plant belonging to the Liliaceae family, has been widely used for biomedical and pharmaceutical application. Its popularity stems from several of its bioactive components that have anti-oxidant, anti-microbial, anti-inflammatory and even immunomodulatory effects. Given such unique multi-modal biological impact, AV has been considered as a biomaterial for regenerative medicine and tissue engineering applications, where tissue repair and neo-angiogenesis are vital. This review outlines the growing scientific evidence that demonstrates the advantage of AV as tissue engineering scaffolds. We particularly highlight the recent advances in the application of AV-based scaffolds. From a tissue engineering perspective, it is pivotal that the implanted scaffolds strike an appropriate foreign body response to be well-accepted in the body without complications. Herein, we highlight the key cellular processes that regulate the foreign body response to implanted scaffolds and underline the immunomodulatory effects incurred by AV on the innate and adaptive system. Given that AV has several beneficial components, we discuss the importance of delving deeper into uncovering its action mechanism and thereby improving material design strategies for better tissue engineering constructs for biomedical applications.